Enhanced particle method with stress point integration for simulation of incompressible fluid-nonlinear elastic structure interaction - Falahaty, Hosein; Khayyer, Abbas; Gotoh, Hitoshi (Journal of fluids and structures, 2018)
A fully-Lagrangian particle-based computational method is developed for simulation of incompressible Fluid, non-linear Structure Interaction (FSI) with incorporation of stress point integration (Randles and Libersky, 2005) to resolve instabilities related to zero-energy modes. Structural dynamics is founded on discretization of the divergence of stress according to Moving Least Squares (MLS) method. The stress point integration is incorporated in calculation of structural dynamics, resulting in a Dual Particle Dynamics (DPD) structure model (Randles and Libersky, 2005). A structure model based on nodal integration is also considered for comparison and simply referred to as MLS. The DPD and MLS structure models are coupled with an enhanced projection-based Moving Particle Semi-implicit (MPS) method as the fluid model, resulting in DPD–MPS and MLS–MPS FSI solvers, respectively. The enhanced performance of DPD with respect to MLS is first shown through a set of tests for structure model. Then the superior performance of DPD–MPS FSI solver with respect to MLS–MPS one is demonstrated through a set of FSI benchmark tests. The present study also presents a new algorithm for fluid–structure coupling via components of stress tensors in surface boundary stress points. [Display omitted] •Stress point integration is utilized in particle-based modeling of FSI.•Nonlinear structure models with nodal and stress point integrations are compared.•The structure models are coupled with enhanced MPS-based fluid model.•By setting stress points on the boundaries, a new version of coupling is achieved.•Clear improvements are obtained in suppressing zero energy modes in FSI modeling.